Evaluation Of Anthropometric Measurements For Physical Development Of Early Age Futsal Players: A Case Study Of Kuantanamo Futsal Academy - Amiq, Fahrial; Angga, Prayogi Dwina; Hariyoko; Hariyanto, Eko; Fatoni, Rizal Ahmad (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2025)
Sports science is one of the fields of sports science that can help sports develop and coach each athlete. Phenomena and problems that occur during the training process in the field can be solved by applying sports science based on data obtained scientifically; this data record assists coaches in determining and providing the proper method for their athletes. One way to use sports science in the field is by measuring the anthropometry of Kuantanamo Futsal Academy students. This study aimed to determine and examine anthropometric measurements in Kuantanamo Futsal Academy students aged 7-10 years. This study uses a quantitative method. This type of research is observational and test. To collect data on student anthropometric measurements that are to be known include a) height, b) weight, c) skin fat, and d) BMI. The subjects in this study were Kuantanamo futsal academy students aged 7-10 years, totaling 20 students. The anthropometric measurements of Kuantanamo Futsal Academy students obtained the following average: height 145.8, weight 41.24, skin fat 14.85, categorized as underfoot (mild level), BMI 19.3, classified as ideal. This can be a reference for coaches to determine what programs should be carried out so that students get treatment appropriate to their body condition.